Analisis Faktor Penghambat Pemahaman Simbol Perbandingan Matematika Anak Usia Dini - Rosifah Rosifah (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Tarbiyah dan Keguruan, Universitas Islam Bandung., 2025)
This study aims to identify the factors that hinder children’s understanding of the use of the less-than (<) and greater-than (>) comparison symbols, as well as to examine teachers’ perceptions of the obstacles affecting children’s ability to comprehend these comparison concepts at TK Pertiwi 49, Semarang City. The research employed a qualitative approach with data collected through guided interviews. The findings indicate that difficulties in understanding comparison symbols stem from children’s limited cognitive abilities, a lack of concrete learning media, and instructional methods that are insufficiently varied. In addition, individual differences in children’s developmental levels also influence their understanding of comparison concepts using symbols. Teachers perceive that the use of teaching aids, play-based learning approaches, contextual examples, and intensive guidance can enhance children’s understanding.